2017
DOI: 10.1021/acs.chemrestox.6b00219
|View full text |Cite
|
Sign up to set email alerts
|

Application of 2-Aminothiazoline-4-carboxylic Acid as a Forensic Marker of Cyanide Exposure

Abstract: Cyanides are infamous for their highly poisonous properties. Accidental cyanide poisoning occurs frequently, but occasionally, intentional poisonings also occur. Inhalation of fumes generated by fire may also cause cyanide poisoning. There are many limitations in direct analysis of cyanide. 2-Aminothiazoline-4-carboxylic acid (ATCA), a cyanide metabolite, seems to be the only surrogate that is being used in the detection of cyanide because of its stability and its cyanide-dependent quality in a biological matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 21 publications
1
19
2
Order By: Relevance
“…As presented in Table 3 , the ATCA blood concentrations of victims of fire incidents ranged from 100 to 191 ng/mL in previous reports. 16 However, our results revealed higher ATCA blood concentration levels. Although the reason for this was not discussed in this study, there may have been a difference in the periods between CN exposure and death or a racial difference in the metabolism of CN to ATCA.…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…As presented in Table 3 , the ATCA blood concentrations of victims of fire incidents ranged from 100 to 191 ng/mL in previous reports. 16 However, our results revealed higher ATCA blood concentration levels. Although the reason for this was not discussed in this study, there may have been a difference in the periods between CN exposure and death or a racial difference in the metabolism of CN to ATCA.…”
Section: Resultscontrasting
confidence: 64%
“…The endogenous and exogenous levels of CN and ATCA in the human blood are presented in Table 3 . 10 , 15 , 16 , 28 , 34 − 36 It became apparent that the present methods can be applied to the concentration ranges of fire incidents and CN poisoning and are satisfactory for forensic purposes. The raw data of the calibrants and QC samples are presented in Tables S2 and S3 .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…However, the high volatility and short half-life (t 1/2 = 0.34 -1.28 hours) of cyanide narrow the detection window for successful analysis [19]. Previous studies also revealed that cyanide concentration fluctuates over time and at various temperatures upon storage [20,21]. These create a challenge for the confirmation of exposure due to the difficulty in interpreting the cyanide concentration.…”
Section: Introductionmentioning
confidence: 99%